TEATER BANGSAWAN MUDA, FORMULA PERTUNJUKAN DRAMA MELAYU BANGSAWAN MASA KINI - Afriadi, Deni (Jurnal Ilmu Budaya, 2019)
Malay “Bangsawan” drama is believed to the embryo of the development of theatre in Riau province. From its history, Bangsawan drama owed to Indian traders who brought wayang Parsi to Malay Peninsula (Malaysia, Sumatera, and to Temasik (Singapore)). Malay “Bangsawan” drama nowdays undergoes changes. The “Bangsawan” drama changes the existed convention which differentities it from the “old Bangsawan” is then called the “new Bangsawan”. This change is beneficial for the continuity of “Malay Bangsawan” drama because a good performance should be able to adapt with the social condition. This writing views how the changes in form and structure occur in Malay “Bangsawan” drama. The changes lead to the term “New (young) Bangsawan Theatre”. Keywords: Malay Bangsawan Drama, New (young) Bangsawan Theatre.